Capsule Retention in Crohn's Disease: A Meta-analysis. Issue 1 (3rd May 2019) - Pasha, Shabana F; Pennazio, Marco; Rondonotti, Emanuele; Wolf, Douglas; Buras, Matthew R; Albert, Jörg G; Cohen, Stanley A; Cotter, Jose; D'Haens, Geert; Eliakim, Rami; Rubin, David T; Leighton, Jonathan A
Abstract : This systematic review showed lower capsule retention rates in suspected and established Crohn's disease than older literature. Retention rates were further reduced after patency capsule and cross-sectional imaging. Retention rates were also lower in pediatric compared with adult Crohn's disease. Abstract: Background: The main factor that limits wider utilization of capsule endoscopy (CE) in Crohn's disease (CD) is the potential risk of retention. The aim of this systematic review was to evaluate capsule retention rates in adult and pediatric CD and determine if retention risk is reduced in established CD (ECD) with patency capsule (PC) or magnetic resonance/computed tomography (MR/CT) enterography. Methods: Studies of CD patients undergoing CE that reported retention were identified. Pooled estimates for retention rates and relative risk in ECD to suspected CD (SCD) were calculated. All hypothesis tests were 2-sided; statistical significance was set at a P value of <0.05. Results: In the overall CD cohort, retention rates were 3.32% (95% confidence interval [CI], 2.62%–4.2%): 4.63% (95% CI, 3.42%–6.25%) and 2.35% (95% CI, 1.31%–4.19%) in ECD and SCD, respectively. Retention rates were 3.49% (95% CI, 2.73%–4.46%) and 1.64% (95% CI, 0.68%–3.89%) in adult and pediatric CD, respectively. Retention risk in adult ECD was 3.4 times higher than SCD, but there was no difference in retention risk in pediatric ECD compared with SCD. Retention rates in ECD were decreased after patency capsule (2.88%; 95% CI, 1.74%–4.74%) and MR/CT enterography (2.32%; 95% CI, 0.87%–6.03%). Conclusions: In comparison with older literature, this meta-analysis demonstrates lower CE retention rates in SCD and ECD. Retention rates in pediatric CD were lower than in adult CD. Retention rates in adult ECD were higher than SCD, but there were no differences between pediatric ECD and SCD. Retention rates in ECD were lower after negative PC or MR/CT enterography.